Phoebe and her unicorn in unicorn theater - Simpson, Dana, 1977- (Kansas City, Missouri : Andrews McMeel Publishing, 2018)
Summer is here, and Phoebe and Marigold are headed to drama camp. At Camp Thespis, Phoebe and friends have their work cut out for them: writing, producing, and acting in an entirely original play! Phoebe's expecting some quality time with her best friend, but in a surprise twist, Marigold has invited her sister, Florence Unfortunate Nostrils!
3.8
3-6
GN300L
Keywords: Girls -- Comic books, strips, etc. -- Fiction; Unicorns -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Girls -- Juvenile fiction; Unicorns -- Juvenile fiction; Friendship -- Juvenile fiction; Fantasy comics; Comics (Graphic works); Graphic novels; Comic books, strips, etc